The Portrait of Nationalism in The Superman Is Dead’s Song, Jadilah Legenda - Puji Lestari; Lambok Hermanto Sihombing (Universitas Negeri Surabaya, 2022)
Music is one of medium to convey a message. Through music, people do not only enjoy the beat but also know what is behind the lyric. Jadilah Legendais one of the songs written by Superman Is Dead (SID), Punk Rock pioneers from Bali. In this scientific study, the authors aim to analyse the portrait of nationalism among Indonesian people depicted in Jadilah Legenda. The qualitative approach is used to analyze the lyrics of its song. The dataset was taken from SID’s official website www.supermanisdead.net and any other journal articles. To support the analysis, the authors apply the Scansion approach from Dennis DeSantis to analyze the stress pattern on the lyrics and Stuart Hall's representation and cultural identity to interpret the message of the song. As a result, the song attempted to portray the nationalism and solidarity of Indonesian people.